Evaluation of the potential of the production of electricity and heat using energy crops with phytoremediation features. (5th November 2017) - Uchman, Wojciech; Skorek-Osikowska, Anna; Werle, Sebastian
Highlights: Experimental research on gasification of the selected energy crops with phytoremediation potential was performed. Thermodynamic and economic analysis of integrated energy system was conducted based on the results of experimental study. The break even price of electricity ranges from 48.41 to 90.05 €/MWh depending on the system size. Abstract: The use of biomass fuels is continually investigated, and the industry application possibilities are widely recognized. In the paper, an experimental investigation of gasification in a fixed-bed atmospheric reactor of selected energy crops is presented. These crops belong to the class of phytoremediation plants, and their potential to combine agroenergetics and active environment improvements is studied. The composition and characteristics of the obtained gas allow its use in an internal combustion engine. Composition of gas obtained from Sida hermaphrodita during the experimental study was used for thermodynamic and economic analysis of a CHP system with a gas engine. The system quality indices were calculated. For the economic analysis, the net present value method was adopted. The break-even price of electricity ( c el b - e ) was calculated. The paper includes a sensitivity analysis of change in the heat and biomass price. The power of the analyzed units was in the range of 1–5 MW in biomass chemical energy. The c el b - e ranges from 90.05 €/MWh (1 MW of supplied chemical energy in biomass) to 48.41 €/MWh (5 MW of supplied chemical energy in biomass).